COMBINING LIQUID CHROMATOGRAPHY WITH TANDEM MASS SPECTROMETRY (LC-MS/MS) TECHNIQUE, SPECTROPHOTOMETERVALIDATION AND AN IN SILICO STUDY OF 96% ETHANOL EXTRACT OF SPIRULINA PLATENSIS - SUSANTININGSIH, TIWUK; FADILAH, FADILAH; PRIJANTI, ANI RETNO; HARDIANY, NOVI SILVIA (International Journal of Applied Pharmaceutics, 2024)
Objective: This study was to analyze the component sofa 96% ethanol extract of Spirulina platensis by the LC-MS/MS technique, then validate them with the spectrophotometer technique using the C-phycocyanin standard and an in silico study approach as an antioxidant property of S. platensis against inflammatory. Methods: Chromatographic resolution was attained with a Phenominex C18 (50 mm×2.6 mm, 3 µm) stationary column technique, validation using C-phycocyanin standard using the spectrophotometer technique, and an in silico study of c-phycocyanin using molecular docking analysis. Results: Tentative active compounds such as flavonoid (Maltol and Morin), peptide (Cyclo Pro-Ala, Cyclo Pro-Pro, and Thymine), and phenol (m-Aminophenol, N-Methyltyramine, and Tyramine) have been identified from a 96% ethanol extract of S. platensis by LCMS/MS analysis. The concentration of c-phycocyanin in the 96% ethanol extract of S. platensis is 229, 2µg/ml. According to our in silico study, c-phycocyanin demonstrates potential as an anti-inflammatory agent. Conclusion: The LC-MS/MS technique can detect flavonoid, peptide, and phenolic components in the 96% ethanol extract of S. platensis. A spectrophotometer can identify the validation equation of c-phycocyanin in a 96% ethanol extract of S. platensis. Based on our in silico study, c-phycocyanin demonstrate the capability to prevent inflammatory activity.